The Impact of Paternity Leave on Employee Productivity in the Workplace: A Quantitative Study in Malaysia - Ren, Sim Jia; Siew, Han Kok (Electronic Journal of Business and Management, 2023)
Paternity leave is one of the topics discussed in society in this era. Paternity leave is also a benefit provided by the organisation and has been written into the law in other countries. However, Malaysia still has no law that states paternity leave, and not all organisations provide paternity leave to their employee. Maslow’s Hierarchy of Needs Theory, Expectancy Theory and Herzberg’s Two Factory Theory were adopted and incorporated in this study. A cross-sectional study is conducted whereby the data gathered is from the collection of questionnaires as the main instrument. The data was collected through an online survey. Participants of this study included 147 male individuals, 18 years old and above with working experience. The data collected was further analysed using SPSS software for descriptive statistics for each variable. The independent variable, namely: Paternity leave, had a significant effect on all the dependent variables, namely: Employee Productivity, Organisation Productivity and Employee Satisfaction. This study is crucial to guide other researchers in understanding better paternity leave in Malaysia. It is also beneficial for organisations, especially since management will start to provide paternity leave to their employees.